Las terapias cognitivas : mitos y aspectos controvertidos (2010)
ABSTRACT: This paper focuses on four mysths and controversial issues about cognitive therapy. The first of these controversial issues it is the idea that cognitives therapies are just technique of cognitive restructuring that belongs to the behavior modifications therapies, and that because this is does not have its own theoretical model or a methodology. The second contentious issue refere to the idea that for the cognitive therapies the cause of human behavior and emotions is just the thiking process. The third controversial issue originates on the false idea that cognitive therapists disrespect their patiens by imposes their criteria on them. For the discussion of the fourth contentious issue it is showed as untrue that the cognitive therapies forget human beings non-rational aspects, and that they do not pretend to turn humans into cold and logical processors of information.